Resolving Conflicts, Sustaining Livelihoods: A Fisheries Resource Management Model for Enhancing Fishermen’s Welfare - Nisari, Tika; Siburian, Juliana Pebrina; Anugerah, Tirta; Adiprayoga, Shofian Nanda (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyse the effect of capture fisheries resources and conflict resolution on fishermen's welfare in the coastal area of Sibolga City, as well as to explore the moderating role of conflict resolution in the relationship between capture fisheries resources and fishermen's welfare. The study used a quantitative approach with data collection through questionnaires administered to active fishermen in coastal areas, and analysed using linear regression and moderation tests. The results showed that capture fisheries resources and conflict resolution had a significant effect on fishermen's welfare, but conflict resolution did not act as a moderating variable between capture fisheries resources and fishermen's welfare. These findings emphasise the importance of effective fisheries resource management and conflict resolution strategies as efforts to improve fishermen's welfare. This study has implications for the government and related institutions to strengthen fisheries resource management, improve conflict resolution capacity, and design sustainable development programmes that support the welfare of coastal communities.